Ecosocial effects of community participatory tsetse (Glossina spp.) (Diptera Glossinidae) and bovine trypanosomiasis management at Luke, Southwestern Ethiopia (Bollettino di zoologia agraria e bachicoltura, 2024)
Suppression of tsetse (Glossina spp.) populations and trypanosomiasis infection of infected cattle using mass trapping and trypanocidal drug treatment were carried out in the area of Luke in Southwestern Ethiopia. Adaptive management of the ecosocial system was conducted during the course of the programme to enhance sustainability. The results obtained during 2006 were combined with previously analyzed data from the period of 1995-2005 and interpreted with respects to ecological, economic and social dimensions. Tsetse fly populations and trypanosomias prevalence were greatly reduced, initial indications of potential overstocking of cattle were alleviated slightly, while cattle productivity (calving rates and milk production) improved and oxen for ploughing land increased. Improved animal husbandry and crop production increased income that allowed greater investmentsin improved housing, a school and the continuation of the tsetse control operations. The latter two factors suggest the development of an evolving social organization not evident in 1995. The increased school attendance also reflects ongoing social change in the community. On the negative side, the continued high stocking rate of cattle threatens the ecological capital of the grazing land. In addition, the entry of an external investor in agricultural lands in 2006 added further complexity to the system. To avoid negative effects on economic and social capital, the Luke community has to find an agreement with the external investor who leased landfor crop production. The human population increased by 44% since 1995 making a reproductive health program an increasingly important component in maintaining sustaining rural development. This will require on-going adaptive management of the system for the public good.
Keywords: Tsetse; mass trapping; bovine trypanosomiasis; adaptive management; animal health; sustainability; ecological, economic and social capital